Small-particle-size platinum-based intermetallic compound fuel cell cathode catalyst and preparation method thereof
The in-situ anchoring Pt-based nanoparticles by FeNx sites derived from nitrogen-rich porous carbon is solved, and the problem of nanoparticles growing in high-temperature heat treatment of Pt-based intermetallic compound catalysts is achieved, and the preparation of high-efficiency low-Pt catalysts is achieved, which improves the utilization rate and catalytic activity of Pt atoms.
Patent Information
- Application Number
- CN202411703994.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the proton exchange membrane fuel cell (PEMFC) cathode Pt-based intermetallic compound catalyst grows in the high-temperature heat treatment process, resulting in low Pt atom utilization rate and decreased activity.
The Pt-based nanoparticles are anchored in situ by abundant FeNx sites derived from nitrogen-rich porous carbon, strengthening the interaction between the carrier and the alloy, inhibiting the growth of particles, and forming a 2.3nm Pt-based ordered alloy.
While retaining a stable and orderly structure, the utilization rate of Pt atoms is effectively improved, and the preparation of high-efficiency low-Pt catalysts is realized, which significantly improves the catalytic activity and stability.
Smart Images

Figure CN119786624A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field, and in particular relates to a small-particle platinum-based intermetallic compound fuel cell cathode catalyst and a preparation method thereof. Background Art
[0002] As the core technology of hydrogen energy conversion system, the development and application of proton exchange membrane fuel cells (PEMFCs) are of great significance. At present, PEMFC is mainly limited by the cost problem caused by the limited reserves of precious metal Pt resources. According to the estimation of the U.S. Department of Energy, Pt group metals will be the main cost (accounting for about 40% of the total cost) after large-scale production of fuel cells, and the reduction of Pt group metal loading often leads to the sacrifice of fuel cell device performance and poor stability. Therefore, it is extremely challenging to achieve efficient and stable operation of low Pt cathode catalyst performance.
[0003] Among them, Pt-based intermetallic compounds are considered to be an effective strategy to reduce Pt dosage and improve structural stability due to their ordered structure and unique electronic structure. However, the high-temperature ordered heat treatment process often leads to the growth of Pt-based alloy nanoparticles, resulting in a decrease in the utilization rate of Pt atoms. Existing technologies can effectively inhibit the agglomeration of nanoparticles of Pt-based intermetallic compounds during high-temperature heat treatment by means of carbon layer coating, porous confinement, non-metallic element anchoring, and metal oxide coating, thereby improving the utilization rate of Pt atoms. Hyeon's team used the polydopamine coating method to prepare PtFe nanoparticles with smaller particle sizes. The nitrogen-doped carbon layer formed by the in-situ carbonization of polydopamine during the heat treatment process effectively inhibited the aggregation of nanoparticles, keeping their size at around 6nm. The presence of this carbon layer can also effectively inhibit the agglomeration of PtFe intermetallic nanoparticles under harsh fuel cell conditions, greatly improving the ORR catalytic activity and stability. Liang Haiwei's team used the sulfur anchoring method to enhance the strong metal-support interaction between Pt-based nanoparticles and carbon carriers, and achieved the formation of 46 ordered intermetallic compounds less than 5nm under high temperature conditions up to 1000℃, and achieved excellent activity and stability under low Pt dosage conditions in actual fuel cells. Huang Wenyu's team synthesized PtZn intermetallic nanoparticles loaded on multi-walled carbon nanotubes by sacrificial mesoporous silica shell method, with a particle size distribution range of 3.2±0.4nm. The mesoporous silica shell provides a closed environment for the growth of metal nanoparticles, which can prevent them from agglomerating during high-temperature annealing, which is conducive to the preparation of intermetallic compounds with smaller particles and narrower particle size distribution. After these modifications, although the Pt-based metal compound nanoparticles are controlled below 10nm, they still remain at around 5nm. In addition, factors such as the excessively thick carbon layer, organic poisoning, and difficulty in removing metal oxides in the above method will cause some active sites in the Pt-based alloy to be buried, resulting in low atomic utilization and decreased activity. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a small-particle-size platinum-based intermetallic compound fuel cell cathode catalyst.
[0007] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a small-particle platinum-based intermetallic compound fuel cell cathode catalyst, characterized in that: comprising:
[0008] Ammonia water is added to a mixed solution of water and ethanol, and a tetraethyl silicate solution is added, and magnetic stirring is performed for 3 to 6 hours to obtain a white solid, which is centrifuged, washed three times with a mixed solution of ethanol and water, and dried in an oven overnight to obtain a silica hard template;
[0009] The zinc nitrate hexahydrate and the silicon dioxide hard template are ultrasonically dispersed in methanol, 2-methylimidazole dissolved in methanol is added, and the mixture is stirred for 12 to 24 hours to obtain a white solid, which is centrifuged and washed three times with ethanol. After drying, the solid is heat-treated in an inert atmosphere to obtain a dark blue solid, followed by alkali washing and suction filtration to obtain a black solid. The solid after alkali washing is treated with acid, and porous carbon is obtained by suction filtration, washing, and drying.
[0010] Porous carbon is used as a carrier, and aqueous solutions containing platinum and iron or cobalt or nickel are added respectively, stirred overnight, and a catalyst precursor is obtained after rotary evaporation. The catalyst precursor is heat-treated and then acid-treated to obtain the small-particle platinum-based intermetallic compound fuel cell cathode catalyst.
[0011] As a preferred embodiment of the preparation method of the present invention, wherein: the ammonia water is added to a mixed solution of water and ethanol, wherein the volume ratio of water to ethanol is 1:1 to 1:5.
[0012] As a preferred embodiment of the preparation method of the present invention, the rotation speed of the centrifugal separation is 8000-12000 rpm and the time is 1-5 min.
[0013] As a preferred embodiment of the preparation method of the present invention, the zinc nitrate hexahydrate and the silicon dioxide hard template are ultrasonically dispersed in methanol, and 2-methylimidazole dissolved in methanol is added, wherein the mass ratio of zinc nitrate hexahydrate to silicon dioxide is 3:1 to 3:10, and the mass of the added 2-methylimidazole is 3 to 10 g.
[0014] As a preferred embodiment of the preparation method of the present invention, the drying is followed by heat treatment in an inert atmosphere, wherein the inert atmosphere is argon or nitrogen; the heating rate of the heat treatment is 1 to 10°C / min, the heat treatment temperature is 800 to 1000°C, and the heat treatment time is 0.5 to 3h.
[0015] As a preferred embodiment of the preparation method of the present invention, the solid after alkali washing is subjected to acid treatment, wherein the solution used for alkali washing is a sodium hydroxide solution with a molar concentration of 1 to 6 M; the acid treatment solution is a dilute sulfuric acid or dilute hydrochloric acid solution with a molar concentration of 0.1 to 1 M.
[0016] As a preferred embodiment of the preparation method of the present invention, the aqueous solutions of platinum and iron or cobalt or nickel are aqueous solutions of chloroplatinic acid and aqueous solutions of ferric chloride or cobalt chloride or nickel chloride, respectively.
[0017] As a preferred embodiment of the preparation method of the present invention, the catalyst precursor is heat-treated, wherein the heating rate of the heat treatment is 5 to 15°C / min, the heat treatment temperature is 250 to 1100°C, and the heat treatment time is 2 to 4h.
[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a small-particle platinum-based intermetallic compound fuel cell cathode catalyst, characterized in that the particle size of the small-particle platinum-based intermetallic compound fuel cell cathode catalyst is ≤2.3nm.
[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a small-particle platinum-based intermetallic compound fuel cell cathode catalyst for use in a proton exchange membrane fuel cell.
[0020] Beneficial effects of the present invention:
[0021] The present invention generates rich FeN through nitrogen-rich porous carbon xThe Pt-based nanoparticles are anchored in situ, thereby strengthening the interaction between the carrier and the alloy, effectively inhibiting the growth of the particles, and the Pt-based ordered alloy formed is only 2.3nm. The prepared catalyst effectively improves the utilization rate of Pt atoms while retaining a stable ordered structure, realizing the preparation of high-efficiency low-Pt catalysts. The preparation method is simple, low-cost, and has good reproducibility, and the platinum-based alloy catalyst prepared based on this method shows excellent catalytic activity in the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0023] Figure 1 This is a transmission electron microscope image of a small-particle platinum-based intermetallic compound fuel cell cathode catalyst prepared in Example 1 of the present invention;
[0024] Figure 2 The particle size distribution result of nanoparticles in the cathode catalyst of small-particle platinum-based intermetallic compound fuel cell prepared in Example 1 of the present invention;
[0025] Figure 3 Elemental analysis results of a single nanoparticle in the cathode catalyst of a small-particle platinum-based intermetallic compound fuel cell prepared in Example 1 of the present invention;
[0026] Figure 4 This is an X-ray diffraction crystal structure spectrum of a small-particle platinum-based intermetallic compound fuel cell cathode catalyst prepared in Example 1 of the present invention;
[0027] Figure 5 The electrochemical activity area test results of the small-particle platinum-based intermetallic compound fuel cell cathode catalyst prepared in Example 1 of the present invention;
[0028] Figure 6 The stability test results of the small-particle platinum-based intermetallic compound fuel cell cathode catalyst prepared in Example 1 of the present invention in a three-electrode system;
[0029] Figure 7 The graph is the test result of a hydrogen-air fuel cell assembled with the small-particle platinum-based intermetallic compound fuel cell cathode catalyst prepared in Example 1 of the present invention as the cathode. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0033] Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0034] Instruments used in the embodiments of the present invention:
[0035] Rotary evaporator (Shanghai Ailang Instrument Co., Ltd., model CCA-1112A), oven (101A-1E electric heating blower), stirrer (WIGGENSWHMIX 8XL), tube furnace (OTF-1200X), transmission electron microscope (JEM-2100), X-ray diffractometer (Mini Flex 600), X-ray photoelectron spectrometer (K-Alpha).
[0036] Example 1
[0037] This embodiment provides a method for preparing a small-particle-size platinum-based intermetallic compound fuel cell cathode catalyst, comprising the following steps:
[0038] (1) Add 20 mL of ammonia water to a mixed solution of ethanol and water, and use a pipette to transfer 20 mL of tetraethyl silicate to the mixed solution, and stir magnetically at 500 rpm for 5 h at room temperature. Then separate the solid by centrifugation at a speed of 10,000 rpm for 3 min, and dry the obtained solid in an oven at 55°C to obtain a white silica hard template:
[0039] (2) 3 g of zinc nitrate hexahydrate and 2 g of a silica hard template were uniformly dispersed in a methanol solution, and then 6.5 g of dimethylimidazole was added to the dispersion, and stirred at room temperature for 24 h. The solid was then separated by centrifugation, washed three times with ethanol, and dried to obtain a white solid;
[0040] (3) The obtained white solid was placed in a tube furnace and heat treated in an argon atmosphere at a heating rate of 5 °C min -1 , heat treatment temperature is 950℃, time is 1h, and a dark blue solid is obtained;
[0041] (4) washing the pyrolysis product with a 6M sodium hydroxide solution to remove the silica hard template, then treating it with an acid with a 1M dilute sulfuric acid solution to remove excess oxides, and finally filtering, washing, and drying to obtain a carbon support;
[0042] (5) 50 mg of the carbon support was placed in a beaker and dispersed evenly with ethanol. Then 789 μL of chloroplatinic acid solution (7.4 mg Pt mL -1 ) and 8.5 mg of ferric chloride hexahydrate, mixed evenly, and then magnetically stirred at room temperature for 12 h, and a catalyst precursor containing a metal source was obtained by rotary evaporation;
[0043] (6) The obtained catalyst precursor was placed in a tube furnace and heat treated in a 5 vol% argon-hydrogen mixed gas at a heating rate of 10 °C min -1 The heat treatment temperature is 850℃, the time is 2h, and the temperature is 10℃min -1 The cooling rate is reduced to 350°C, and after natural cooling to room temperature, the product is pickled, filtered, and dried to obtain a small-particle platinum-based intermetallic compound fuel cell cathode catalyst.
[0044] The small-particle platinum-based intermetallic compound fuel cell cathode catalyst of Example 1 was characterized by transmission electron microscopy. The results are as follows: Figure 1 As shown, the alloy nanoparticles of the obtained catalyst are uniformly loaded on the surface of the support and no obvious agglomeration occurs after high-temperature heat treatment.
[0045] The particle size statistics of the nanoparticles loaded in the cathode catalyst of the small-particle platinum-based intermetallic compound fuel cell of Example 1 were analyzed. Figure 2 As shown, it was found that the average particle size of the nanoparticles was 2.30 nm, the particle size was small and the distribution was uniform.
[0046] The elemental analysis of the single nanoparticles loaded in the small-size platinum-based intermetallic compound fuel cell cathode catalyst of Example 1 was performed, and the results were as follows: Figure 3 As shown, the particles contain both platinum and iron elements, confirming the successful formation of platinum-iron alloy.
[0047] The X-ray crystal structure of the small-particle platinum-based intermetallic compound fuel cell cathode catalyst of Example 1 was characterized. Figure 4 As shown, the peaks appearing in the spectrum are completely consistent with those of platinum-iron alloy, confirming the synthesis of platinum-based intermetallic compounds.
[0048] The electrochemical active area of the small-particle platinum-based intermetallic compound fuel cell cathode catalyst of Example 1 was tested, and the results were as follows: Figure 5 As shown in the figure, the alloy nanoparticles are small, well dispersed, have high atomic utilization, and the electrochemical active area can reach 123.1m 2 g -1 .
[0049] The small-particle platinum-based intermetallic compound fuel cell cathode catalyst of Example 1 was subjected to an accelerated aging test in a 0.1 mol / L perchloric acid solution. The results are as follows: Figure 6 As shown, the catalyst showed almost no activity decline after 50,000 cycles of accelerated aging test, demonstrating excellent stability.
[0050] A single cell test was conducted on the small-particle platinum-based intermetallic compound fuel cell cathode catalyst of Example 1. Figure 7 As shown in Figure 2, the peak power density of the membrane electrode assembled with a small-particle platinum-based intermetallic compound fuel cell cathode catalyst under hydrogen-air test conditions can reach 845 mW cm -2 , with superior battery performance expression.
[0051] Example 2
[0052] This embodiment provides a method for preparing a small-particle-size platinum-based intermetallic compound fuel cell cathode catalyst, comprising the following steps:
[0053] (1) Add 20 mL of ammonia water to a mixed solution of ethanol and water, and use a pipette to transfer 20 mL of tetraethyl silicate to the mixed solution, and stir magnetically at 500 rpm for 5 h at room temperature. Then separate the solid by centrifugation at a speed of 10,000 rpm for 3 min, and dry the obtained solid in an oven at 55°C to obtain a white silica hard template:
[0054] (2) 3 g of zinc nitrate hexahydrate and 4 g of a silica hard template were uniformly dispersed in a methanol solution, and then 6.5 g of dimethylimidazole was added to the dispersion, and stirred at room temperature for 24 h. The solid was then separated by centrifugation, washed three times with ethanol, and dried to obtain a white solid;
[0055] (3) The obtained white solid was placed in a tube furnace and heat treated in an argon atmosphere at a heating rate of 5 °C min -1 , heat treatment temperature is 950℃, time is 1h, and a dark blue solid is obtained;
[0056] (4) washing the pyrolysis product with a 6M sodium hydroxide solution to remove the silica hard template, then treating it with an acid with a 1M dilute sulfuric acid solution to remove excess oxides, and finally filtering, washing, and drying to obtain a carbon support;
[0057] (5) 50 mg of carbon support was placed in a beaker and evenly dispersed with ethanol. Then 789 μL of chloroplatinic acid solution (7.4 mg Pt mL -1 ) and 8.5 mg of ferric chloride hexahydrate, mixed evenly, and then magnetically stirred at room temperature for 12 h, and a catalyst precursor containing a metal source was obtained by rotary evaporation;
[0058] (6) The obtained catalyst precursor was placed in a tube furnace and heat treated in a 5 vol% argon-hydrogen mixed gas at a heating rate of 10 °C min -1 The heat treatment temperature is 850℃, the time is 2h, and the temperature is 10℃min -1 The cooling rate is reduced to 350°C, and after natural cooling to room temperature, the product is pickled, filtered, and dried to obtain a small-particle platinum-based intermetallic compound fuel cell cathode catalyst.
[0059] The small-particle platinum-based intermetallic compound fuel cell cathode catalyst of Example 2 was subjected to transmission electron microscopy characterization, particle size statistics, elemental analysis, X-ray crystal structure characterization, three-electrode stability test, and single cell performance test, and the results were similar to those of Example 1.
[0060] Example 3
[0061] This embodiment provides a method for preparing a small-particle-size platinum-based intermetallic compound fuel cell cathode catalyst, comprising the following steps:
[0062] (1) Add 20 mL of ammonia water to a mixed solution of ethanol and water, and use a pipette to transfer 20 mL of tetraethyl silicate to the mixed solution, and stir magnetically at 500 rpm for 5 h at room temperature. Then separate the solid by centrifugation at a speed of 10,000 rpm for 3 min, and dry the obtained solid in an oven at 55°C to obtain a white silica hard template:
[0063] (2) 3 g of zinc nitrate hexahydrate and 2 g of a silica hard template were uniformly dispersed in a methanol solution, and then 6.5 g of dimethylimidazole was added to the dispersion, and stirred at room temperature for 24 h. The solid was then separated by centrifugation, washed three times with ethanol, and dried to obtain a white solid;
[0064] (3) The obtained white solid was placed in a tube furnace and heat treated in an argon atmosphere at a heating rate of 5 °C min -1 , heat treatment temperature is 950℃, time is 1h, and a dark blue solid is obtained;
[0065] (4) washing the pyrolysis product with a 6M sodium hydroxide solution to remove the silica hard template, then treating it with an acid with a 1M dilute sulfuric acid solution to remove excess oxides, and finally filtering, washing, and drying to obtain a carbon support;
[0066] (5) 50 mg of carbon support was placed in a beaker and evenly dispersed with ethanol. Then 789 μL of chloroplatinic acid solution (7.4 mg Pt mL -1 ) and 10.5 mg of ferric chloride hexahydrate, mixed evenly, and then magnetically stirred at room temperature for 12 h, and a catalyst precursor containing a metal source was obtained by rotary evaporation;
[0067] (6) The obtained catalyst precursor was placed in a tube furnace and heat treated in a 5 vol% argon-hydrogen mixed gas at a heating rate of 10 °C min -1 The heat treatment temperature is 850℃, the time is 2h, and the temperature is 10℃min -1 The cooling rate is reduced to 350°C, and after natural cooling to room temperature, the product is pickled, filtered, and dried to obtain a small-particle platinum-based intermetallic compound fuel cell cathode catalyst.
[0068] The small-particle platinum-based intermetallic compound fuel cell cathode catalyst of Example 3 was subjected to transmission electron microscopy characterization, particle size statistics, elemental analysis, X-ray crystal structure characterization, three-electrode stability test, and single cell performance test, and the results were similar to those of Example 1.
[0069] Example 4
[0070] This embodiment provides a method for preparing a small-particle-size platinum-based intermetallic compound fuel cell cathode catalyst, comprising the following steps:
[0071] (1) Add 20 mL of ammonia water to a mixed solution of ethanol and water, and use a pipette to transfer 20 mL of tetraethyl silicate to the mixed solution, and stir magnetically at 500 rpm for 5 h at room temperature. Then separate the solid by centrifugation at a speed of 10,000 rpm for 3 min, and dry the obtained solid in an oven at 55°C to obtain a white silica hard template:
[0072] (2) 3 g of zinc nitrate hexahydrate and 2 g of a silica hard template were uniformly dispersed in a methanol solution, and then 6.5 g of dimethylimidazole was added to the dispersion, and stirred at room temperature for 24 h. The solid was then separated by centrifugation, washed three times with ethanol, and dried to obtain a white solid;
[0073] (3) The obtained white solid was placed in a tube furnace and heat treated in an argon atmosphere at a heating rate of 5 °C min -1, heat treatment temperature is 950℃, time is 1h, and a dark blue solid is obtained;
[0074] (4) washing the pyrolysis product with a 6M sodium hydroxide solution to remove the silica hard template, then treating it with an acid with a 1M dilute sulfuric acid solution to remove excess oxides, and finally filtering, washing, and drying to obtain a carbon support;
[0075] (5) 50 mg of carbon support was placed in a beaker and evenly dispersed with ethanol. Then 789 μL of chloroplatinic acid solution (7.4 mg Pt mL -1 ) and 8.5 mg of ferric chloride hexahydrate, mixed evenly, and then magnetically stirred at room temperature for 12 h, and a catalyst precursor containing a metal source was obtained by rotary evaporation;
[0076] (6) The obtained catalyst precursor was placed in a tube furnace and heat treated in a 5 vol% argon-hydrogen mixed gas at a heating rate of 10 °C min -1 The heat treatment temperature is 1050℃, the time is 2h, and the temperature is 10℃min -1 The cooling rate is reduced to 350°C, and after natural cooling to room temperature, the product is pickled, filtered, and dried to obtain a small-particle platinum-based intermetallic compound fuel cell cathode catalyst.
[0077] The small-particle platinum-based intermetallic compound fuel cell cathode catalyst of Example 4 was subjected to transmission electron microscopy characterization, particle size statistics, elemental analysis, X-ray crystal structure characterization, three-electrode stability test, and single cell performance test, and the results were similar to those of Example 1.
[0078] Comparative Example 1
[0079] This embodiment provides a method for preparing a cathode catalyst of a platinum-based intermetallic compound fuel cell, comprising the following steps:
[0080] (1) 12.0 g of Vulcan XC-72 was placed in a 500 mL round-bottom flask, 200 mL of 2.0 M hydrochloric acid was added, and the mixture was heated in an oil bath at 120° C., refluxed for 10 hours, filtered, and washed. The Vulcan XC-72 treated with hydrochloric acid was added to a 500 mL round-bottom flask, 200 mL of 5.0 M nitric acid was added, and the mixture was heated in an oil bath at 120° C., refluxed for 10 hours, filtered, washed, and vacuum dried to obtain the Vulcan XC-72 carbon support to be used.
[0081] (2) Take 100.0 mg of carbon carrier in a 100 mL beaker, add 10.0 mL of ethanol and disperse by ultrasonic. Prepare 50.0 mL of 0.02 M H2PtCl6 solution, FeCl3 solution, CoCl2 solution, NiCl2 solution, and MnCl2 solution. Prepare 50.0 mL of 0.10 M citric acid solution. Take 2.0 mL of the mixed solution and 2.0 mL of the citric acid solution in a 100 mL beaker and stir for five minutes. Take an appropriate amount of dilute ammonia water and titrate to a neutral pH. Add this solution to the dispersed carbon carrier, disperse by ultrasonic for 30 minutes, impregnate the metal salt precursor, then evaporate to dryness under magnetic stirring at 85 ° C, and grind to obtain a black catalyst precursor solid powder.
[0082] (3) The tube furnace is heated to a certain temperature, Ar gas is passed through for 30 minutes to exhaust the air in the tube, the black solid powder obtained by impregnation of the metal salt precursor is placed in a quartz boat, and quickly pushed into the heating center of the tube furnace for rapid high-temperature carbon thermal reduction for a certain period of time, and then the porcelain boat placed in the heating center is quickly pushed out for rapid cooling. The carbon thermal reduction temperature is set to 800°C and the carbon thermal reduction time is set to 70 minutes to obtain a platinum-based intermetallic compound fuel cell cathode catalyst. The size of the catalyst synthesized by this preparation method is measured to be above 4nm.
[0083] The present invention aims at solving the problems of nanoparticle growth and low atomic utilization rate caused by high-temperature heat treatment in the ordering process of Pt-based intermetallic compound catalysts in the cathode of proton exchange membrane fuel cells (PEMFC) in the prior art. The present invention provides a small-particle Pt-based intermetallic compound fuel cell cathode catalyst, which in situ anchors Pt-based nanoparticles through rich FeNx sites derived from nitrogen-rich porous carbon, strengthens the interaction between the carrier and the alloy, and effectively inhibits the growth of particles. The formed Pt-based ordered alloy is only 2.3nm. The prepared catalyst effectively improves the Pt atomic utilization rate while retaining a stable ordered structure, realizes the preparation of high-efficiency and low-Pt catalysts, and effectively solves the above-mentioned technical problems.
[0084] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a small-particle platinum-based intermetallic compound fuel cell cathode catalyst, characterized in that: include, Ammonia water is added to a mixed solution of water and ethanol, and a tetraethyl silicate solution is added, and magnetic stirring is performed for 3 to 6 hours to obtain a white solid, which is centrifuged, washed three times with a mixed solution of ethanol and water, and dried in an oven overnight to obtain a silica hard template; The zinc nitrate hexahydrate and the silicon dioxide hard template are ultrasonically dispersed in methanol, 2-methylimidazole dissolved in methanol is added, and the mixture is stirred for 12 to 24 hours to obtain a white solid, which is centrifuged and washed three times with ethanol. After drying, the solid is heat-treated in an inert atmosphere to obtain a dark blue solid, followed by alkali washing and suction filtration to obtain a black solid. The solid after alkali washing is treated with acid, and porous carbon is obtained by suction filtration, washing, and drying. Porous carbon is used as a carrier, and aqueous solutions containing platinum and iron or cobalt or nickel are added respectively, stirred overnight, and a catalyst precursor is obtained after rotary evaporation. The catalyst precursor is heat-treated and then acid-treated to obtain the small-particle platinum-based intermetallic compound fuel cell cathode catalyst.
2. The preparation method according to claim 1, characterized in that: The ammonia water is added into a mixed solution of water and ethanol, wherein the volume ratio of water to ethanol is 1:1 to 1:
5.
3. The preparation method according to claim 1, characterized in that: The rotation speed of the centrifugal separation is 8000-12000 rpm, and the time is 1-5 minutes.
4. The preparation method according to claim 1, characterized in that: The zinc nitrate hexahydrate and the silicon dioxide hard template are ultrasonically dispersed in methanol, and 2-methylimidazole dissolved in methanol is added, wherein the mass ratio of the zinc nitrate hexahydrate to the silicon dioxide is 3:1-3:10, and the mass of the added 2-methylimidazole is 3-10g.
5. The preparation method according to claim 1, characterized in that: After drying, heat treatment is performed in an inert atmosphere, wherein the inert atmosphere is argon or nitrogen; the heating rate of the heat treatment is 1 to 10°C / min, the heat treatment temperature is 800 to 1000°C, and the heat treatment time is 0.5 to 3h.
6. The preparation method according to claim 1, characterized in that: The solid after alkali washing is subjected to acid treatment, wherein the solution used for alkali washing is a sodium hydroxide solution with a molar concentration of 1 to 6M; the acid treatment solution is a dilute sulfuric acid or dilute hydrochloric acid solution with a molar concentration of 0.1 to 1M.
7. The preparation method according to claim 1, characterized in that: The aqueous solutions of platinum and iron or cobalt or nickel are respectively aqueous chloroplatinic acid solution and aqueous solution of ferric chloride or cobalt chloride or nickel chloride.
8. The preparation method according to claim 1, characterized in that: The catalyst precursor is subjected to heat treatment, wherein the heating rate of the heat treatment is 5-15°C / min, the heat treatment temperature is 250-1100°C, and the heat treatment time is 2-4h.
9. A small-particle platinum-based intermetallic compound fuel cell cathode catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The particle size of the small-particle platinum-based intermetallic compound fuel cell cathode catalyst is ≤2.3 nm.
10. Use of the small-particle platinum-based intermetallic compound fuel cell cathode catalyst as claimed in claim 9 in a proton exchange membrane fuel cell.
Citation Information
Patent Citations
Method for synthesizing a small-size high-dispersion intermetallic compound catalyst material and application
CN110649273A
Fuel cell electrocatalyst and preparation method and application thereof
CN112510221A
Preparation method of nitrogen-doped mesoporous carbon supported Pt fuel cell cathode catalyst
CN114899437A
Preparation method of ultralow platinum cathode catalyst for fuel cell
CN115275233A
Preparation method and application of small-size platinum-based ordered alloy fuel cell catalyst
CN117133934A
Cited By
Lead-modulated high-poisoning-resistance intermetallic compound bifunctional catalyst as well as preparation method and application thereof
CN120243059A
Lead-modified bifunctional intermetallic catalysts with high resistance to poisoning, their preparation methods and applications
CN120243059B